Interrelationships among knowledge management, organisational learning and innovation. (11th February 2011) - Kanchana, Rapee; Law, Kris M.Y.; Comepa, Narongsak; Malithong, Prichaya; Phusavat, Kongkiti
This study aims to describe the interrelationships among knowledge management, organisational learning and innovation. This description potentially helps a company's preparation for the application of the quality management award. The Thailand Quality Award highlights the interrelationships among knowledge management, workforce focus and leadership as they contribute to learning and innovation, continuous performance improvement and organisational competitiveness. A total of 35 manufacturing firms completed and returned the survey. The interviews with chief quality officers were also conducted to help interpret the survey's findings. The results show that effective knowledge management will lead to better learning and subsequently more innovativeness in an organisation. These results also indicate the importance of leadership in establishing supportive cultures and working environment for effective knowledge management.